Comparative Judgement for Linking Two Existing Scales - Benton, Tom (Frontiers in Education, 2021)
This article describes an efficient way of using comparative judgement to calibrate scores from different educational assessments against one another (a task often referred to as test linking or equating). The context is distinct from other applications of comparative judgement as there is no need to create a new achievement scale using a Bradley-Terry model (or similar). The proposed method takes advantage of this fact to include evidence from the largest possible number of examples of students’ performances on the separate assessments whilst keeping the amount of time required from expert judges as low as possible. The paper describes the method and shows, via simulation, how it achieves greater accuracy than alternative approaches to the use of comparative judgement for test equating or linking.